Diseño de un sistema de asistencia eléctrica para bicicletas de montaña (2024)
The transportation of goods and services is an important activity in the productive chain of society, because this activity ensures that the produced goods reach the final consumer. The greenhouse gases (GHG) generated by vehicles with internal combustion engines cause this part of the supply chain to generate negative environmental impacts [1]. Therefore, alternatives with low environmental impact in transportation, such as the use of bicycles, become attractive to minimize the carbon footprint; however, using this means of transportation becomes challenging according to the topography of the place traveled.